2014
DOI: 10.1088/0953-8984/26/46/464104
|View full text |Cite
|
Sign up to set email alerts
|

Soft matter strategies for controlling food texture: formation of hydrogel particles by biopolymer complex coacervation

Abstract: Soft matter physics principles can be used to address important problems in the food industry. Starch granules are widely used in foods to create desirable textural attributes, but high levels of digestible starch may pose a risk of diabetes. Consequently, there is a need to find healthier replacements for starch granules. The objective of this research was to create hydrogel particles from protein and dietary fiber with similar dimensions and functional attributes as starch granules. Hydrogel particles were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 41 publications
5
78
0
Order By: Relevance
“…In this case, the dense viscoelastic polymer-rich phase is referred to as the coacervate phase (de Kruif et al, 2004;Schmitt & Turgeon, 2011;Turgeon, Schmitt, & Sanchez, 2007). In our previous work, we showed that micron-sized hydrogel microspheres could be formed by electrostatic complexation of gelatin and pectin, and that these particles had potential for use as texture-modifiers to replace fat droplets or starch granules (Wu et al, 2014). The texture-modifying abilities of electrostatic complexes have also been reported in earlier studies (Laneuville, Paquin, & Turgeon, 2000Schmitt & Turgeon, 2011).…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…In this case, the dense viscoelastic polymer-rich phase is referred to as the coacervate phase (de Kruif et al, 2004;Schmitt & Turgeon, 2011;Turgeon, Schmitt, & Sanchez, 2007). In our previous work, we showed that micron-sized hydrogel microspheres could be formed by electrostatic complexation of gelatin and pectin, and that these particles had potential for use as texture-modifiers to replace fat droplets or starch granules (Wu et al, 2014). The texture-modifying abilities of electrostatic complexes have also been reported in earlier studies (Laneuville, Paquin, & Turgeon, 2000Schmitt & Turgeon, 2011).…”
Section: Introductionsupporting
confidence: 53%
“…2). The type A gelatin has an isoelectric point (pI) around pH 7 to 9, which explains the positive charges on the gelatin molecules at pH 3 to 7 observed in this study (Djagny et al, 2001;Wu et al, 2014). The charge on the gelatin molecules decreases as the pH increases due to conversion of eNH þ 3 groups to eNH 2 groups (reduced positive charge) and of eCOOH groups to eCOO À groups (increased negative charge).…”
Section: Influence Of Ph On the Electrical Properties Of Gelatin And mentioning
confidence: 53%
See 2 more Smart Citations
“…The self-assembly of these materials is driven by entropy, where the initial electrostatic attraction between oppositely-charged macro-ions results in the release of small, bound counter-ions and the restructuring of water molecules [1][2][3][4]. Complex coacervates have a long history of use in the food [5][6][7][8][9][10][11][12][13] and personal care [14,15] industries, and have found increasing utility as a platform for drug and gene delivery [1][2][3][4], as well as underwater adhesives [5][6][7][8][9][10][11][12][13][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. Coacervation has also recently been implicated in the formation of various biological assemblies [1,[14][15][16]55,…”
Section: Introductionmentioning
confidence: 99%